Electrode-particle impacts - Sokolov, S (2017)
The thesis is concerned with the study of particles by impact voltammetry. The use of the particle-impact technique is developed and extended beyond quantitative sizing of spherical metallic nanoparticles to complex systems involving quasi-spherical nanoparticles, reversible agglomeration processes and extremely low levels of analyte. Initially the assumption that the particles are spherical is challenged and a system of quasi-spherical citrate-capped nanoparticles has been analyzed. The combination of SEM imaging and electrochemical nano-impact experiments was demonstrated to allow sizing and characterization of the geometry of single silver nanoparticles and determine an icosahedral geometry. Next the agglomeration/aggregation state of silver nanoparticles is studied in a media of high ionic strength. Distinguishing agglomeration (reversible clustering of the particles) and aggregation (irreversible clustering) is a challenging task for conventional techniques, especially at arbitrary concentrations. Using the nano-impact technique in conjunction with light scattering techniques (nanoparticle tracking analysis and dynamic light scattering) it was demonstrated that even in high ionic strength environments, particles develop equilibria between agglomerated and monomeric species, which in practice means the transport behavior is dominated by the presence of fast-diusing monomers with high chemical reactivity. Having developed an understanding of the agglomeration and aggregation state of the particles and underlying mass transport, the causes of agglomeration were considered and developed using the idea of entropy of mixing driven clustering, a concept hitherto unexplored and an entirely new perspective. Through the use of maximization of entropy of mixing the expected agglomeration population in the absence of any enthalpy eects and the contribution to the entropy from the formation of dimers, trimers etc., was predicted even though their formation causes an overall reduction in particle numbers. For a system of citrate-capped silver nanoparticles entropy was shown to play a dominant role in the observed size distributions. The distribution predicted by the model and the experimentally observed particle size distributions demonstrated the strong entropy contribution. The last chapter is concerned with the design of an approach for the most sensitive electrochemical detection of nanoparticles, yet realized. The limit of detection is dependent on the mass transport of the particles to the electrode and the electroactive area of the electrode. The use of a hydrodynamic walljet flow causes high mass transport. Larger electroactive area increases the observed current magnitude but in order to detect individual particles low capacitance is a required and as a result traditional macroelectrodes cannot be used. Hence in order to increase the surface area and reduce the associated increase in capacitance we chose to use a random assembly of microelectrodes (RAM) which consist of hundreds of carbon fiber microelectrodes connected in parallel to a current collector, which results in large electroactive area and relatively low capacitance. Using this in-house manufactured cell we were able to demonstrate femtomolar limit of detection for 50 nm silver citrate-capped nanoparticles, which is substantially the lowest limit detection reported in the literature to date.